Peningkatan Kepatuhan Pajak Melalui Sosialisasi Perpajakan kepada Komunitas Bisnis Multi-Level Marketing Minyak Aroma Terapi di Yogyakarta - Solichah, Nurviani; Utomo, Rochmad Bayu (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to evaluate the effectiveness of tax socialization in improving tax compliance among the multi-level marketing (MLM) business community of aromatherapy oil in Yogyakarta. The research employs a qualitative approach using in-depth interviews, direct observation, and documentation methods. The results indicate that despite high participant enthusiasm, there is a gap in tax compliance. Out of 25 participants, 5 individuals did not possess a Taxpayer Identification Number (NPWP), while 15 out of 20 participants with an NPWP had not reported their MLM income. Limited understanding of tax administrative obligations emerged as a key factor. The tax socialization methods employed, including face-to-face and online approaches, had their respective advantages and drawbacks. Face-to-face socialization was perceived as more interactive, whereas online socialization offered flexibility. This study recommends more intensive educational approaches and follow-up mentoring programs to assist participants in comprehending and fulfilling their tax obligations correctly. These findings are expected to serve as a reference for the government and tax authorities in designing more effective tax socialization strategies to enhance tax compliance, particularly among small and medium-sized enterprise segments